Abundance of Endophytic Bacteria in Sauropus androgynus and Evaluation of Chitinolytic Activity - Sri Ayu Anggita (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This study aimed to isolate and evaluate the biological safety and potential of endophytic bacteria from Sauropus androgynus (katuk) and their Chitinolytic activity for use as biological agents. A total of 14 endophytic bacterial isolates were obtained from different plant parts: 5 from the roots (T1, T2, T3, T4, P14), 5 from the stems (T7, T8, T9, T10, T11), and 4 from the leaves (T5, P6, KB12, T13). The safety of these isolates was assessed through hypersensitivity (HR) and hemolysis (HL) tests. In the HR test, none of the isolates induced necrotic symptoms in tobacco leaves, indicating they are not pathogenic to plants. In the HL test, two bacterial which were T4 from roots and T5 from leaves, isolates were found to produce clear zones on blood agar, indicating α-hemolysin production. However, the other isolates did not form hemolysis zones, suggesting they are safe for mammals. Antibacterial activity against the plant pathogen Ralstonia solanacearum was evaluated using spot inoculation methods. The results showed that none of the isolates were able to inhibit the growth of R. solanacearum. Further testing revealed that one bacterial isolate which was T8 obtained from the stem produced chitinase, as evidenced by the formation of a clear zone around the bacterial colony on chitin-containing media.